Research on improved scheme of resource public key infrastructure data synchronization - Feng LENG; Qi ZHAO; Zhiwei YAN; Yu ZENG (网络与信息安全学报)
RPKI Relying party needs to synchronizing data from repository periodically to verify information.In general, Rsync and RRDP are the two common means to complete data synchronization, however, each of them has related problems.In order to solve these problems, through analyzingthe way for synchronizing data from repository by the relying party, a mathematical model was established.Furthermore, based on the current problems faced by the two synchronization means, an improved RPKI data synchronization scheme was proposed.The advantages and disadvantages of the improved scheme were analyzed in detail, as well as the applicable scenarios.The improved scheme could provide a reference for optimizing the deployment and application of RPKI.